1997
DOI: 10.1097/00007890-199702150-00023
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia, but Not Reoxygenation, Induces Interleukin 6 Gene Expression Through Nf-??B Activation1

Abstract: Interleukin (IL) 6 is one of major mediators of inflammation, and IL-6 gene activation during hypoxia/reoxygenation has been implicated in the pathogenesis of ischemia/reperfusion injury. However, molecular events involved in IL-6 gene expression during hypoxia/reoxygenation remain to be identified. We have previously shown that NF-kappa B plays an essential and indispensable role in the transcriptional activation of the IL-6 gene induced by various stimuli, including IL-1 and tumor necrosis factor-alpha. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…Indeed, NF-κB activated by ROS is markedly activated during ischemia, and the inhibition of XOD by the preadministration of allopurinol strongly diminished NF-κB activation (Matsui et al, 2000). Some reports have also revealed that NF-κB was activated during hypoxia, but not reoxygenation (Muraoka et al, 1997;Ricciardi et al, 2000). Moreover, we also demonstrated in this experiment that NF-κB was activated during ischemia, but not after reperfusion (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, NF-κB activated by ROS is markedly activated during ischemia, and the inhibition of XOD by the preadministration of allopurinol strongly diminished NF-κB activation (Matsui et al, 2000). Some reports have also revealed that NF-κB was activated during hypoxia, but not reoxygenation (Muraoka et al, 1997;Ricciardi et al, 2000). Moreover, we also demonstrated in this experiment that NF-κB was activated during ischemia, but not after reperfusion (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown that NAC abolishes hypoxia-induced NF-B DNA-binding activity (26). In the present study, the antioxidants NAC (500 M) and PDTC (10 M) abolished NF-B DNA-binding activity and TNF-␣ mRNA levels in J774.1 cells FIGURE 5.…”
Section: Hypoxia Induction Of Nf-b Dna Binding and Tnf-␣ Mrna Requiresupporting
confidence: 52%
“…Hydrogen peroxide exposure can rapidly activate NF-B, and the thiol reductant pyrrolidinedithiocarbamic acid (PDTC), an effective antioxidant, can block NF-B activation in response to LPS, TNF-␣, and active phorbol ester in a number of different cell lines (24,25). The antioxidant N-actylcysteine (NAC) blocks activation of NF-B by hypoxia (26). However, these previous reports did not measure endogenous ROS production or describe the source of ROS generation required for the activation of NF-B by hypoxia or LPS (27).…”
Section: Ultiple Organ System Failure (Mosf)mentioning
confidence: 99%
“…HIF-1 has not been implicated in the regulation of MMP-9, although some in vitro studies have found this enzyme to be induced by hypoxia (18)(19)(20). The induction of MMP-9 may be due to NF-B induced by hypoxia (21,22). The correlation between HIF-1 and MMP-9 raises the possibility that HIF-1 may have a regulatory role in the expression of MMP-9.…”
Section: Discussionmentioning
confidence: 99%